Association between steroid dosage and death with a functioning graft after kidney transplantation - Opelz, Gerhard; Döhler, Bernd (American journal of transplantation, 2013)
Death with a functioning graft remains a major challenge following kidney transplantation. Steroid dosing may be a modifiable risk factor. Collaborative Transplant Study (CTS) data were analyzed to assess the relationship between long-term steroid dose and death with function during years 2-5 posttransplant in 41 953 adult recipients of a deceased-donor kidney transplant during 1995-2010. Steroid dose at year 1 correlated significantly with death with function overall, and with death due to cardiovascular disease or infection (all p < 0.001). In patients with optimal graft function (serum creatinine <130 µmol/L) and no anti-rejection treatment during (a) year 1 (b) years 1 and 2, these significant associations remained (all p < 0.001). The center-specific incidence of steroid withdrawal during year 2 showed a significant inverse association with death due to cardiovascular disease (p < 0.001) or infection (p < 0.001) overall, and within the subpopulation with good graft function and no rejection during year 1 (p = 0.002 and p < 0.001, respectively). Maintenance steroid dose shows a highly significant association with death with a functioning graft caused by cardiovascular disease or infection during years 2-5 after kidney transplantation, even in patients with good graft outcomes in whom steroid treatment would appear to be unnecessary.
Gesehen am 09.12.2021